Race to invade: Understanding soft tissue integration at the transmucosal region of titanium dental implants. Issue 5 (May 2021) - Guo, Tianqi; Gulati, Karan; Arora, Himanshu; Han, Pingping; Fournier, Benjamin; Ivanovski, Sašo
Graphical abstract: Abstract: Objectives: The success of a dental implant system not only depends on appropriate osseointegration at the bone-implant interface, but also on robust soft-tissue integration (STI)/muco-integration at the transmucosal region. However, numerous studies have reported that the STI quality of conventional smooth and bio-inert titanium-based transmucosal components is significantly inferior to that of natural teeth, which may compromise the long-term success of implant restorations. In this review article, we discuss the structural and histological characteristics of peri-implant tissues; compare the roles of various cells residing in the transmucosal region and explore the material-based challenges that must be addressed to achieve early establishment and long-term maintenance of STI. Methods: This extensive review article critically compares and contrasts the findings from articles published in the domain of 'soft-tissue integration around Ti dental implants'. Results: Histological characteristics, including poorer epithelial attachment and absence of direct collagen-implant/abutment integration, are responsible for the inferior STI strength around dental implants/abutments. Furthermore, various cellular functions during STI establishment and maturation at the abutment-mucosa interface must be modulated to achieve early STI. Moreover, we discuss and detail the challenges of achieving robust STI, including the presence of oral bacterial milieu, as well as material and corrosion related issues. Finally, research challenges towards achieving and maintaining robust STI are discussed, targeting the future directions to enhance the long-term survival of implant restorations. Significance: Based on its histological characteristics, STI on current implant/abutment surfaces is suboptimal compared to the periodontal attachment found at teeth, making implants potentially more susceptible to disease initiation and progression. To obtain stable STI at the trasmucosal region, it is essential for future studies to design customized implant systems, with enhanced surface bioactivity and tailorable therapeutic capacity, which can improve the long-term success of implant restorations, especially in compromised conditions.